2019
DOI: 10.1016/j.bbrc.2019.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and prevention of cartilage degeneration surrounding a focal chondral defect in the porcine model

Abstract: Focal defects in articular cartilage are unable to self-repair and, if left untreated, are a leading risk factor for osteoarthritis. This study examined cartilage degeneration surrounding a defect and then assessed whether infilling the defect prevents degeneration. We created a focal chondral defect in porcine osteochondral explants and cultured them ex vivo with and without dynamic compressive loading to decouple the role of loading. When compared to a defect in a porcine knee four weeks post-injury, this mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…It is worth noting that a prior study, using a similar focal chondral defect model, showed cartilage degradation by sGAG loss along the defect's edge when higher strains were applied (i.e. 20% strain vs 10% strain used herein) [43]. Thus, it is possible that a higher strain environment could lead to more pronounced differences between infilling and would require a mechanically supportive structure to maintain the health of the cartilage tissue adjacent to the defect.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…It is worth noting that a prior study, using a similar focal chondral defect model, showed cartilage degradation by sGAG loss along the defect's edge when higher strains were applied (i.e. 20% strain vs 10% strain used herein) [43]. Thus, it is possible that a higher strain environment could lead to more pronounced differences between infilling and would require a mechanically supportive structure to maintain the health of the cartilage tissue adjacent to the defect.…”
Section: Discussionmentioning
confidence: 81%
“…It is feasible that the 3D + CMH, under free swelling conditions, may have produced a similar result through forces generated by the scaffold swelling within the defect. It was previously reported that swelling resulting from a hydrogel that was in situ polymerized in a focal chondral defect, generated pressures ranging from 13 to 310 kPa depending on the hydrogel formulation [43]. This swelling pressure correlated to a protective phenomenon, which minimized sGAG loss that was observed in empty defects.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…However, PCL is often composited with other polymers to overcome its hydrophobicity [ 25 , 26 ]. Hydrogels are highly absorbent, act as a buffer between the scaffold and the cartilage, and prevent cartilage degeneration [ 27 ]. It has been reported that alginate, a biocompatible polysaccharide extracted from seaweed, is widely used in cartilage regeneration, with excellent biocompatibility, injectability, and ability to support encapsulated cells differentiation, and can be quickly gelled by the addition of Ca 2+ [ 14 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%